ASD-Associated De Novo Mutations in Five Actin Regulators Show Both Shared and Distinct Defects in Dendritic Spines and Inhibitory Synapses in Cultured Hippocampal Neurons - Hlushchenko, Iryna; Khanal, Pushpa; Abouelezz, Amr; Paavilainen, Ville O.; Hotulainen, Pirta (Frontiers in Cellular Neuroscience, 2018)
Many actin cytoskeleton-regulating proteins control dendritic spine morphology and density, which are cellular features associated with autism spectrum disorder (ASD). Recent studies using animal models show that autism-related behavior can be rescued by either manipulating actin regulators or by reversing dendritic spine density or morphology. Based on these studies, the actin cytoskeleton is a potential target pathway for developing new ASD treatments. Thus, it is important to understand how different ASD-associated actin regulators contribute to the regulation of dendritic spines and how ASD-associated mutations modulate this regulation. For this study, we selected five genes encoding different actin-regulating proteins and induced ASD-associated de novo missense mutations in these proteins. We assessed the functionality of the wild-type and mutated proteins by analyzing their subcellular localization, and by analyzing the dendritic spine phenotypes induced by the expression of these proteins. As the imbalance between excitation and inhibition has been suggested to have a central role in ASD, we additionally evaluated the density, size and subcellular localization of inhibitory synapses. Common for all the proteins studied was the enrichment in dendritic spines. ASD-associated mutations induced changes in the localization of α-actinin-4, which localized less to dendritic spines, and for SWAP-70 and SrGAP3, which localized more to dendritic spines. Among the wild-type proteins studied, only α-actinin-4 expression caused a significant change in dendritic spine morphology by increasing the mushroom spine density and decreasing thin spine density. We hypothesized that mutations associated with ASD shift dendritic spine morphology from mushroom to thin spines. An M554V mutation in α-actinin-4 (ACTN4) resulted in the expected shift in dendritic spine morphology by increasing the density of thin spines. In addition, we observed a trend towards higher thin spine density with mutations in myosin IXb and SWAP-70. Myosin IIb and myosin IXb expression increased the proportion of inhibitory synapses in spines. The expression of mutated myosin IIb (Y265C), SrGAP3 (E469K) and SWAP-70 (L544F) induced variable changes in inhibitory synapses.